The Young Socialist : a magazine of justice & love (Grays (Essex): Mr. & Mrs. Glasier Foster, 1919)
"Redactie: Jas. Paulden, G. Prietsley, A. Russell Drukker/Drukkerij: Andrew Fleming, Main Street 384, Shettleston, GlasgowPeriodiciteit: maandelijks"